Features of Group Discussion in In-person and Online Focus Groups - Olga T. Melnikova; Ekaterina M. Nesterova (Lomonosov Moscow State University, 2024)
Background. Today, there is a trend towards the introduction of online communication in the field of scientific research. The development of this trend in social psychology was accelerated by the COVID-19 pandemic and by the requirements of social distancing. These conditions make it difficult to apply qualitative methods in in-person format. The use of online focus groups became relevant for researchers even before the outbreak of the pandemic. However, now the practical importance of studying online focus groups is only increasing. Objectives. The aim of the study is to identify the features of group discussion in in-person and online focus groups. Study Participants. 29 people (27.9 % men, 72.41 % women) from 18 to 25 years old (M = 21.1; SD = 1.95) participated in in-person focus groups, and 24 people (37.5 % men, 62.5 % women) from 18 to 26 years old (M = 22.8; SD = 2.15). Methods. The study involves qualitative content analysis of 10 transcripts of focus groups conducted in face-to-face and online formats between 2019 and 2021. Results. As a result of qualitative content analysis, categories that reflect the features of interaction between participants at each stage of the group discussion in online and in-person focus groups were identified. The features of group discussion in in-person and online focus groups are revealed. Conclusions. (1) In in-person focus groups, self-orientation is observed only at the beginning of the discussion, while in online focus groups, it prevails throughout the discussion; (2) in in-person focus groups, participants' focus on others is expressed in frequent interaction and in asking participants questions; in online groups it manifests itself in giving participants the opportunity to express their opinions and in paying attention to other opinions; (3) in online focus groups, unlike in-person focus groups, participants do not have a psychological community of group members; (4) the effect of group discussion in in-person focus groups is an attempt to reach a single "average" opinion on the issue under discussion, whereas in online focus groups, the aim is in deepening discussion of the topic.